Overlay welding analysis on GTAW and SMAW processes in terms of mechanical properties and corrosion rate - Ahmad Fikrie; Wiwik Dwi Pratiwi; Ardani Ahsanul Fakhri (Journal of Engineering and Applied Technology, 2022)
The Overlay welding process is a coating technique that is carried out using the welding process. In this study, a coating was conducted on carbon SA 516 gr. 70 with stainless steel electrodes. Welding was carried out with the GTAW and SMAW processes. The electrode used in the first coating for GTAW was ER309L while for SMAW was E309L. The next coating used in the GTAW electrode was ER316L and the SMAW electrode was E316L. In both welding processes, testing was carried out on mechanical properties and corrosion rates. Testing was carried out to determine mechanical properties, namely bending testing. This was done based on ASME IX. Bending test results in both processes are declared accepted because there are no defects. In testing the corrosion rate using the three-electrode cell method based on the ASTM G102 Overlay welding process with GTAW has a slower corrosion rate of 0.00890 MMPY compared to the overlay welding process with SMAW.